Influence of quality customer service management in employees satisfaction in public organization : A case of Sengerema District Council – Mwanza - Anthony, Adrian (Mzumbe University, 2025)
A dissertation Submitted to Mzumbe University as a partial fulfillment of the requirement for the award of Masters of Business Administration (MBA-CM) of Mzumbe University